Evaluating the Correlation between the Body Mass Index (BMI) and Dental Age in 6 to 13-Yyear-Old Children - SH Sakhdari; AH JafariNaini; MH kharazi; N Najafi (Islamic Azad University, 2016)
Background and aim: Methods of age estimation with the aid of radiography have higher accuracy compared with other methods. Some investigations have been performed in this regard, but the correlation between dental development and Body Mass Index (BMI) has been limitedly researched. In the present study, the correlation between dental development and BMI in the children referring to the dental school of Islamic Azad University of Tehran was evaluated with the use of panoramic radiography. Materials and methods: In this cross-sectional analysis, panoramic radiographs of 104 children aged 6 to 13 years were evaluated. The date of radiography minus the birth date was used to determine the chronologic age for each child and then, this age was compared with the dental age estimated by the Demirjian method. Afterwards, the height and weight of the children were measured and the BMI was calculated for each subject. The difference between the estimated dental age and the chronologic age of the subjects was analyzed according to gender and BMI classification. Statistical analyses were performed using the ANOVA test, Pearson correlation coefficient and linear regression. Results: In the 104 samples, the difference between the estimated dental age and the chronologic age was not significant (p=0.516). The dental age in normal weight children was lower than the chronologic age while in obese children, it was higher than the chronologic age (p=0.00001). The correlation coefficient of the estimated dental age using the Demirjian method and the chronologic age in normal weight and obese boys was 0.936 and 0.901, respectively, while in normal weight and obese girls, it equaled 0.916 and 0.942, respectively. Conclusion: The results of the present study showed that dental development is accelerated in obese children.